Amish of Birch Creek : A Love Made New - Book 3 - Fuller, Kathleen (Nashville, Tennessee : Thomas Nelson, 2016)
"Abigail thinks she's lost her chance at love, but with God all things--even love--can be made new"--
Keywords: Amish -- Fiction; Mate selection -- Fiction; Self-realization in women -- Fiction; Man-woman relationships -- Fiction; Christian fiction; Love stories